2023
DOI: 10.3390/ijms241311039
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolomic Analyses Reveal Differences in Flavonoid Pathway Gene Expression Profiles between Two Dendrobium Varieties during Vernalization

Abstract: Dendrobium (Orchidaceae, Epidendoideae) plants have flowers with a wide variety of colors that persist for a long period throughout the year. The yellow coloration of Dendrobium flowers is mainly determined by the flavonol pathway and the flavone pathway, but the relevant biosynthesis mechanisms during vernalization remain unclear. To explore the similarities and differences in flavonoid biosynthesis in different tissues during vernalization, we selected two species of Dendrobium for a flower color study: Dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Additionally, we discovered that PrAO and AST are also essential genes in this pathway in H. serrata . Furthermore, it was found that p-Coumaroyl-CoA, caffeoyl quinic acid, CHI , and CHS were identified as key metabolites and key genes in the antioxidant pathway, which aligns with previous reports ( Liu et al., 2022 ; Shu et al., 2023 ). Moreover, this study revealed that p-Coumaroyl quinic acid, 4-Coumaroylshikimate, 2,3-Dihydrofisetin, HCT , and CYP89A are newly discovered crucial metabolites and crucial genes.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, we discovered that PrAO and AST are also essential genes in this pathway in H. serrata . Furthermore, it was found that p-Coumaroyl-CoA, caffeoyl quinic acid, CHI , and CHS were identified as key metabolites and key genes in the antioxidant pathway, which aligns with previous reports ( Liu et al., 2022 ; Shu et al., 2023 ). Moreover, this study revealed that p-Coumaroyl quinic acid, 4-Coumaroylshikimate, 2,3-Dihydrofisetin, HCT , and CYP89A are newly discovered crucial metabolites and crucial genes.…”
Section: Discussionsupporting
confidence: 90%
“…However, the differentiation in molecular mechanisms controlling the polysaccharide content between diploid and tetraploid D. officinale has remained unknown. A few studies have conducted transcriptome analyses for D. officinale considering different growth stages (juvenile to adult) [41], different plant parts (leaves, stems and roots) [43], flowers [57], and 2-year-old stems [58], and there have been studies on other Dendrobium species, such as D. huoshanense [57,59,60], D. catenatum [61], and D. moniliforme [62]. Therefore, this study has investigated transcriptomic profiles and some key genes related to polysaccharide biosynthesis tetraploid D. officinale.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways are related to carbohydrate metabolism. The up-regulated DEGs in the BP vs. AP comparison for the top 20 KEGG pathways were significantly enriched in the spliceosome (121), mRNA surveillance pathway (86), glycolysis/gluconeogenesis (81), viral carcinogenesis (78), ribosome biogenesis in eukaryotes (70), phagosome and herpes simplex infection (57), and galactose metabolism (51) (Figure S4a). The down-regulated DEGs in the BP vs. AP comparison were significantly enriched in ribosome (312), biosynthesis of amino acids (218), protein processing in the endoplasmic reticulum (203), RNA transport (178), ribosome biogenesis in eukaryotes (115), and phagosome (82).…”
Section: Go and Kegg Of Degs Annotation And Enrichment Analysismentioning
confidence: 99%
“…Transcriptomic and metabolic analyses elucidated that some genes played vital roles in the transition from carbohydrate to alkaloid synthesis in the stems of D. nobile, such as DnAROG, DnPYK, DnDXS, DnACEE, and DnHMGCR [12]. Combined transcriptome and metabolome analysis revealed that DnPHT1 was one of the key genes regulating flavonoid biosynthesis in D. nobile [13]. Transcriptome analysis revealed that some genes like DnPMR6, DnPECS-2.1, DnSS1, and DnGLU3 led to an increase in the biosynthesis of polysaccharides in D. nobile [9].…”
Section: Introductionmentioning
confidence: 99%